Adenosine Deaminase Acting on RNA 1 (ADAR1) Suppresses the Induction of Interferon by Measles Virus - Li, Zhiqun (American Society for Microbiology, 2012)
ADAR1, the interferon (IFN)-inducible adenosine deaminase acting on RNA, catalyzes the C-6 deamination of adenosine (A) to produce inosine (I) in RNA substrates with a double-stranded character. Because double-stranded RNA is a known inducer of IFN, we tested the role of ADAR1 in IFN induction following virus infection. HeLa cells made stably deficient in ADAR1 (ADAR1(kd)) were compared to vector control (CON(kd)) and protein kinase PKR-deficient (PKR(kd)) cells for IFN-β induction following infection with either parental (wild-type [WT]) recombinant Moraten vaccine strain measles virus (MV) or isogenic knockout mutants deficient for either V (V(ko)) or C (C(ko)) protein expression. We observed potent IFN-β transcript induction in ADAR1(kd) cells by all three viruses; in contrast, in ADAR1-sufficient CON(kd) cells, only the C(ko) mutant virus was an effective inducer and the IFN-β RNA induction was amplified by PKR. The enhanced IFN-β transcript-inducing capacity of the WT and V(ko) viruses seen in ADAR1-deficient cells correlated with the enhanced activation of PKR, IFN regulatory factor IRF3, and activator of transcription ATF2, reaching levels similar to those seen in C(ko) virus-infected cells. However, the level of IFN-β protein produced was not proportional to the level of IFN-β RNA but rather correlated inversely with the level of activated PKR. These results suggest that ADAR1 functions as an important suppressor of MV-mediated responses, including the activation of PKR and IRF3 and the induction of IFN-β RNA. Our findings further implicate a balanced interplay between PKR and ADAR1 in modulating IFN-β protein production following virus infection.